Essays on demography-driven inequality and the long-run welfare consequences of government intervention - Laps, Jochen (2016)
This dissertation analyzes the scope for reducing demography-driven income and wealth inequality. In the first two chapters, we focus on the projected aftermath of the demographic transition, in which a stationary population, stochastic and deterministic in turn, can save for old age and make gifts within the family. Exploiting the link between ex post inequality and ex ante uncertainty, we determine the long-run optimal size of alternative Social Security arrangements, which trades off insurance of lifetime income against the crowding out of capital. We find that, once ex ante insurance is taken into account, Social Security is welfare-improving in the long run, as long as capital is not too productive and the transfer motive is not too strong. Chapter 4 addresses a transitional regime in a dualistic economy. We analyze the impact of demographic developments in relation to the evaluation of the social profitability of India’s rural roads project, known as Pradhan Mantri Gram Sadak Yojana (PMGSY). We find that PMGSY has large long-run effects on rural welfare through its influence on health and education. Improvements in rural living-conditions make human capital less likely to exit rural areas, which further contributes to the overall welfare gains of PMGSY.